Effects of enhanced downwelling of NOx on Antarctic upper-stratospheric ozone in the 21st century - Maliniemi, V; Nesse Tyssøy, H; Smith-Johnsen, C; Arsenovic, P; Marsh, DR (Copernicus Publications, 2021)
Ozone is expected to fully recover from the chlorofluorocarbon (CFC) era by the end of the 21st century. Furthermore, because of anthropogenic climate change, a cooler stratosphere decelerates ozone loss reactions and is projected to lead to a super recovery of ozone. We investigate the ozone distribution over the 21st century with four different future scenarios using simulations of the Whole Atmosphere Community Climate Model (WACCM). At the end of the 21st century, the equatorial upper stratosphere has roughly 0.5 to 1.0 ppm more ozone in the scenario with the highest greenhouse gas emissions compared to the conservative scenario. Polar ozone levels exceed those in the pre-CFC era in scenarios that have the highest greenhouse gas emissions. This is true in the Arctic stratosphere and the Antarctic lower stratosphere. The Antarctic upper stratosphere is an exception, where different scenarios all have similar levels of ozone during winter, which do not exceed pre-CFC levels. Our results show that this is due to excess nitrogen oxides (NOx) descending faster from above in the stronger scenarios of greenhouse gas emissions. NOx in the polar thermosphere and upper mesosphere is mainly produced by energetic electron precipitation (EEP) and partly by solar UV via transport from low latitudes. Our results indicate that the thermospheric/upper mesospheric NOx will be important factor for the future Antarctic ozone evolution and could potentially prevent a super recovery of ozone in the upper stratosphere.